Celebrating Al and Rose Watkins' 40th Wedding Anniversary - Watkins, Howard::::::::: (1983)
Adam Watkins, Rose Watkins holding Robin Watkins in baby blanket seated; Howard Watkins and Christine Watkins standing 207 Geneva Ave. #B